Bacterioplankton community responses and the potential ecological thresholds along disturbance gradients - Xuan, Lixia; Sheng, Zheliang; Lu, Jiaqi; Qiu, Qiongfen; Chen, Jiong; Xiong, Jinbo (The Science of the total environment, 2019)
Increasing intensity and frequency of coastal pollutions are the trajectory to be expected due to anthropogenic pressures. However, it is still unclear how and to what extent bacterioplankton communities respond to the two factors, despite the functional importance of bacterioplankton in biogeochemical cycles. In this study, significant organic pollution index (OPI) and offshore distance gradients, as respective proxies of disturbance intensity and disturbance frequency, were detected in a regional scale across the East China Sea. A multiple regression on matrices (MRM) revealed that the biogeography of bacterioplankton community depended on spatial scale, which was governed by local characters. Bacterioplankton community compositions (BCCs) were primarily governed by the conjointly direct (−0.28) and indirect (−0.48) effects of OPI, while offshore distance contributed a large indirectly effect (0.52). A SEGMENTED analysis depicted non-linear responses of BCCs to increasing disturbance intensity and disturbance frequency, as evidenced by significant tipping points. This was also true for the dominant bacterial phyla. Notably, we screened 30 OPI-discriminatory taxa that could quantitatively diagnose coastal OPI levels, with an overall 79.3% accuracy. Collectively, the buffer capacity of bacterioplankton communities to increasing disturbance intensity and disturbance frequency is limited, of which the significant tipping points afford a warning line for coastal management. In addition, coastal pollution level can be accurately diagnosed by a few OPI-discriminatory taxa. [Display omitted] •Roles of local variables in governing bacterioplankton assembly are quantified.•Nonlinear responses of bacterioplankton to disturbance intensity and frequency.•The significant tipping points afford a warning line for coastal management.•A few pollution-discriminatory taxa accurately diagnose coastal pollution level.